Development of a multienzyme isothermal and lateral flow dipstick combination assay for the rapid detection of goose astrovirus II - Zhu, Yinchu; Chen, Liu; Xu, Xin; Ye, Weicheng; Ni, Zheng; Huo, Suxin; Hua, Jionggang; Yun, Tao; Yao, Huochun (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionGoose astrovirus (GAstV) is a newly emerging pathogen that is currently widespread among geese, causing visceral gout and leading to substantial gosling mortalities, posing a severe threat to the waterfowl industry. GAstV II is the predominant epidemic strain, characterized by its high morbidity and mortality rate. Consequently, there is an urgent necessity to develop an effective diagnostic approach to control the dissemination of GAstV II, particularly in clinical farms with limited laboratory resources.MethodsIn this study, a novel multi-enzyme isothermal rapid amplification (MIRA) and lateral flow dipstick (LFD) combined assay was developed. Different primers designed specific targeting a highly conserved region within the viral RdRp gene for the detection of GAstV II. Primers optimized and MIRA-LFD assay analyzed its performance regarding limits of detection, specificity, and efficiency of detection.ResultsThe developed MIRA amplification is conducted at a constant temperature and accomplished within 10 minutes. Subsequent naked-eye observation of the LFD strips merely takes 5 minutes. The established MIRA-LFD method exhibits high specificity, with no cross-reaction with other pathogens and attains a detection sensitivity of 1 copy/μl, which is consistent with the reverse transcription quantitative PCR (RT-qPCR) assay. Further evaluation with clinical samples indicates that the accuracy of this MIRA-LFD method correlates well with RT-qPCR for the detection of GAstV II. ConclusionIn summary, the convenience, sensitivity, and rapidity of this newly developed detection method offer a significant advantage for on-site diagnosis of GAstV II.